Eye trauma in boxing - Corrales, G.; Curreri, A. (Clinics in Sports Medicine, 2009)
In boxing, along with a few other sports, trauma is inherent to the nature of the sport; therefore it is considered a high-risk sport for ocular injuries. The long-term morbidity of ocular injuries suffered by boxers is difficult to estimate due to the lack of structured long-term follow-up of these athletes. Complications of blunt ocular trauma may develop years after the athlete has retired from the ring and is no longer considered to be at risk for boxing-related injuries. This article describes the wide range of eye injuries a boxer can sustain, and their immediate and long-term clinical management.